2021
DOI: 10.1002/anie.202100198
|View full text |Cite
|
Sign up to set email alerts
|

Probing Single‐Atom Catalysts and Catalytic Reaction Processes by Shell‐Isolated Nanoparticle‐Enhanced Raman Spectroscopy

Abstract: Developing advanced characterization techniques for single‐atom catalysts (SACs) is of great significance to identify their structural and catalytic properties. Raman spectroscopy can provide molecular structure information, and thus, the technique is a promising tool for catalysis. However, its application in SACs remains a great challenge because of its low sensitivity. We develop a highly sensitive strategy that achieves the characterization of the structure of SACs and in situ monitoring of the catalytic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 57 publications
0
25
1
Order By: Relevance
“…To explore the reaction mechanism, one important and classical reaction that is intensively studied in the field of PMCRs is the plasma-aided reduction of p -nitrothiophenol (PNTP). Previous studies have shown that the transformation of PNTP to p -aminothiophenol (PATP) or p , p ′-dimercaptoazobenzene (DMAB) may take several different pathways, including PNTP to PATP, PNTP to DMAB, DMAB to PATP, and PATP to DMAB. , For instance, it was reported that PNTP can directly transform into DMAB through a four-electron-reduction process or plasmonic heating, while PNTP or DMAB is barely reduced to PATP in the absence of H 2 or NaBH 4 . , More recently, a six-electron photocatalytic reduction process was proposed, where PNTP can be directly converted into PATP on the Ag nanostructures in the presence of the halide anions in an acidic environment owing to the more efficient electron harvesting enabled by the photosensitive halide species . It has been found that many parameters can influence the catalytic activity, such as pH, cations, adsorption orientation, oxygen, wavelength, surface ligands, and crystallinity, sometimes leading to inconsistent observations in different reports.…”
Section: Introductionmentioning
confidence: 99%
“…To explore the reaction mechanism, one important and classical reaction that is intensively studied in the field of PMCRs is the plasma-aided reduction of p -nitrothiophenol (PNTP). Previous studies have shown that the transformation of PNTP to p -aminothiophenol (PATP) or p , p ′-dimercaptoazobenzene (DMAB) may take several different pathways, including PNTP to PATP, PNTP to DMAB, DMAB to PATP, and PATP to DMAB. , For instance, it was reported that PNTP can directly transform into DMAB through a four-electron-reduction process or plasmonic heating, while PNTP or DMAB is barely reduced to PATP in the absence of H 2 or NaBH 4 . , More recently, a six-electron photocatalytic reduction process was proposed, where PNTP can be directly converted into PATP on the Ag nanostructures in the presence of the halide anions in an acidic environment owing to the more efficient electron harvesting enabled by the photosensitive halide species . It has been found that many parameters can influence the catalytic activity, such as pH, cations, adsorption orientation, oxygen, wavelength, surface ligands, and crystallinity, sometimes leading to inconsistent observations in different reports.…”
Section: Introductionmentioning
confidence: 99%
“…The vibrational frequency of ν CN of PIC adsorbed on Pd 2 /Au 4 (2226 cm −1 ) and Pt 2 /Au 4 (2230 cm −1 ) alloy clusters are higher than that of free PIC (2221 cm −1 ), in agreement with the previous experimental and theoretical studies for bimetallic surfaces. 13,56,61 Moreover, we find that the ν CN for PIC adsorption on Pt 6 and Pd 6 (2183 and 2203 cm −1 , respectively) are slightly red-shifted compared to that of free PIC. This red-shift is consistent with the experimental results on the Pd(111) surface but does not agree with the result on the Pt(111) surface (blue-shift).…”
Section: Resultsmentioning
confidence: 69%
“…4-Nitrobenzenethiol (NBT) molecules attached on a metal surface are known to be reductively converted to 4-aminobenzenthiols (ABT) by electrochemical, catalytical, and plasmon-induced photochemical means [30][31][32][33][34] (NBT and ABT are also referred to as para-nitrothiophenol: pNTP and para-aminothiophenol: pATP). This chemical reaction is accompanied with the decrease in the molecular mass; the endgroup of the molecule is converted from NO 2 to NH 2 .…”
Section: Electroreduction Of 4-nitrobenzenethiol (Nbt) On Aumentioning
confidence: 99%
“…In the spectrum taken at 0 V versus Ag/AgCl (very close to the open circuit potential), distinct Raman bands of NBT, e.g., the symmetric stretch of NO 2 at 1340 cm −1 , were clearly observed in the fingerprint region. When the applied potential was shifted negatively, the vibrational features of NBT rapidly decreased, which was followed by the appearance of those of ABT; for example, the frequency of νCC is 1574 cm −1 for NBT and 1590 cm −1 for ABT 34 (the calculated Raman spectra for NBT and ABT are presented in Fig. S3, ESI †).…”
Section: Electroreduction Of 4-nitrobenzenethiol (Nbt) On Aumentioning
confidence: 99%